Efektivitas Pelaksanaan Hak Warga Binaan Perempuan Dalam Mewujudkan Tujuan Pemasyarakatan: Studi Kasus Rumah Tahanan Klas II A Jakarta Timur - Arviani, Cassandra Nadia; Fatony, Achmad; Aditantyo, Antonius; Valerian, Dion; Widigda, Dhurandhara Try; Paladina, Kezia Minar (Jurnal Hukum & Pembangunan, 2015)
The writer(s) of this article try to explain the rights of protection for the people in detention center. Many legal rules made by the state. But practicaly, the authorities in the detention center focused on the liability and responsibility of the prisoners rather then considered about their rights. So, this research group found some findings in their research site at the detention center, about the unfair treatment, discrimination, rights violation, and other mistreatment.